(untitled) (Weinheim, 2013)
This book fills the need for a coherent work combining carefully reviewed articles into a comprehensive overview accessible to research groups and lecturers. In additional to fundamental physics, contributions on topical medical and material science issues are also included.
Keywords: Nuclear physics,Vật lý hạt nhân; Encyclopedias,Bách khoa toàn thư